STUDY OF WORK RELATED RESPIRATORY SYMPTOMS AMONG WELDING WORKERS - Rahmani, Arshad Husain; Al-hurabi, Ali Abbad; Joseph, Rejo Jacob; Babiker, Ali Yousif (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â Objective: The objective of this study was to examine the effect of welding fumes on workers and its correlation with smoking and chewing habits. Methods: A total of 44 occupationally exposed worker of welding material in 10 different units were included in this study. A pre-textured questioner was used to inquire duration of work, smoking, chewing, and health related issue. Moreover, sputum samples were collected for the cytological analysis through papanicolaou staining. Results: The subjects were distributed according to health-related issue, and it was observed that back pain was in 8 subjects (18.18%), respiratory disorder including acute cough was in 4 (9.09%), asthma was noted in 5 (11.36%), vision problem in 4 (9.09%), skin rashes in 5 (11.36%), and other health problem was in 3 (6.81%). Cytological analysis was made and observed that 15 (34.09%) subjects out of 44 showed acute inflammation. In addition, diseases linked with respiratory systems such as asthma, chest tightness/acute cough, and other respiratory problem was high in the workers who have long exposure of the welding materials. Furthermore, the subjects who have a history of smoking, chewing, and long work duration showed a high prevalence of health-related complications. Conclusion: This result is indicating that exposure to welding material for long time causes an alteration in epithelial cells that permit easier attack of microbes and thereby finally causes inflammation.